Splenectomy for sclerosing extramedullary hematopoietic tumor of the spleen - Perdomo, Carolina; Romero, Lucia I; González, Daniel A (Revista Argentina de Cirugía, 2026)
Extramedullary hematopoietic tumors are rare and characterized by the presence of hematopoietic elements at various stages of maturity, atypical megakaryocytes, and fibroblastic proliferation. We report the case of a patient with sclerosing extramedullary hematopoietic tumor of the spleen.The patient was 71-year-old man with a history of hypertension, diabetes, and hepatitis C virus infection. Multiple spleen lesions were identified in imaging tests during workup due to abdominal discomfort. Although a vascular tumor was suspected, laparoscopic splenectomy was decided after considering other possible causes. The pathology examination revealed a sclerosing extramedullary hematopoietic tumor of the spleen, which was confirmed by immunohistochemical tests. These tumors are usually single or, less frequently, multiple lesions affecting different organs and are associated with chronic myeloproliferative syndromes. The histologic confirmation is mandatory due to their similarity to malignant tumors. Extramedullary hematopoietic tumors are rare, and there is little scientific clinical evidence regarding their diagnosis and management. The histological confirmation is mandatory due to their similarity to malignant tumors.